2015
DOI: 10.1109/tit.2015.2457443
|View full text |Cite
|
Sign up to set email alerts
|

Coded Cooperative Data Exchange Problem for General Topologies

Abstract: Abstract-We consider the coded cooperative data exchange problem for general graphs. In this problem, given a graph G = (V, E) representing clients in a broadcast network, each of which initially hold a (not necessarily disjoint) set of information packets; one wishes to design a communication scheme in which eventually all clients will hold all the packets of the network. Communication is performed in rounds, where in each round a single client broadcasts a single (possibly encoded) information packet to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Moreover, long range transmission will result in high power usage and high interference and fading which eliminates the benefits of D2D communications. In [176,177], the authors considered a general setting in which the constraint of a fully connected network is removed allowing the problem to be extended to arbitrary topologies. Using undirected graphs, the authors in [176] provides exact results for the number of transmissions in d-regular networks.…”
Section: Trade-off Of Completion Time and Decoding Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, long range transmission will result in high power usage and high interference and fading which eliminates the benefits of D2D communications. In [176,177], the authors considered a general setting in which the constraint of a fully connected network is removed allowing the problem to be extended to arbitrary topologies. Using undirected graphs, the authors in [176] provides exact results for the number of transmissions in d-regular networks.…”
Section: Trade-off Of Completion Time and Decoding Delaymentioning
confidence: 99%
“…Using undirected graphs, the authors in [176] provides exact results for the number of transmissions in d-regular networks. In [177], the authors show that the polynomial time solution is limited only for some special cases such as the fully connected network. They proved that the general problem is NP-hard and computationally intractable.…”
Section: Trade-off Of Completion Time and Decoding Delaymentioning
confidence: 99%
“…It has been recently shown that a deterministic algorithm based on conditional basis construction [1] can solve this optimization problem with lower complexity. The CDE problem has also been extended in heterogeneous directions, including CDE for arbitrarily connected network [7], [8], successive omniscience and priority [9], [10], and optimization on weighted cost or fairness rate allocations [6], [11], [12].…”
Section: A Related Workmentioning
confidence: 99%
“…(broadcast) 환경에서 네트워크 부호 기반 효과적인 재전송에 대한 연구 [7][8][9][10][11] , 네트워크 상의 노드들이 네 트워크 부호화를 통해 서로 정보를 효과적으로 교환 하는 연구 [12,13] , 그리고 네트워크 부호화 기법을 사용 한 시스템의 에너지 소모에 관한 연구 [14,15] …”
Section: 기법이 소개된 이후 지금까지 주로 브로드캐스트unclassified